Determination of anthropometric and physiological performance measures in elite Scottish female Rugby Union players - Nyberg, C. C.; Penpraze, V. (International Journal of Research in Exercise Physiology, 2016)
Purpose: There is currently a notable absence of available scientific literature on Scottish women`s rugby. To fulfill this niche, the aim of this study is to investigate the anthropometric, and physiological performance measures in Scottish female rugby players. Methods: Nineteen elite women`s rugby union players from Scotland`s top tier division were split into forwards and backs and underwent various anthropometric, and physical performance tests. Results: Mean (± standard deviation) recorded height, weight and body volume among all players is 166.11 cm ± 4.66, 73.51 kg ± 10.60 and 69.61 L ± 9.45, respectively. Average lean weight, fat weight and fat percentage is 51.18 kg ± 5.16, 22.75 kg ± 7.00 and 29.83% ± 6.43. Results from the sit and reach test, the Illinois agility test, 40m sprints and the yo-yo test are 23.18cm ± 9.23, 19.09s ± 0.85, 6.98s ± 0.38, and 35.82 ml·kg-1·min-1 ± 3.02 respectfully. Conclusion: There is no significant difference among forwards and backs in both the anthropometric and physical performance measurements, with the exception of the sit and reach test. The lack of significant difference in weight, body fat percentage and all other physiological performance measures between forwards and backs highlight the need to adapt the squad`s training regime to a more positional-orientated program.